Developmental Aspects of Cardiac Adaptation to Increased Workload - Ostadal, Bohuslav; Kolar, Frantisek; Ostadalova, Ivana; Sedmera, David; Olejnickova, Veronika; Hlavackova, Marketa; Alanova, Petra (Journal of cardiovascular development and disease, 2023)
The heart is capable of extensive adaptive growth in response to the demands of the body. When the heart is confronted with an increased workload over a prolonged period, it tends to cope with the situation by increasing its muscle mass. The adaptive growth response of the cardiac muscle changes significantly during phylogenetic and ontogenetic development. Cold-blooded animals maintain the ability for cardiomyocyte proliferation even in adults. On the other hand, the extent of proliferation during ontogenetic development in warm-blooded species shows significant temporal limitations: whereas fetal and neonatal cardiac myocytes express proliferative potential (hyperplasia), after birth proliferation declines and the heart grows almost exclusively by hypertrophy. It is, therefore, understandable that the regulation of the cardiac growth response to the increased workload also differs significantly during development. The pressure overload (aortic constriction) induced in animals before the switch from hyperplastic to hypertrophic growth leads to a specific type of left ventricular hypertrophy which, in contrast with the same stimulus applied in adulthood, is characterized by hyperplasia of cardiomyocytes, capillary angiogenesis and biogenesis of collagenous structures, proportional to the growth of myocytes. These studies suggest that timing may be of crucial importance in neonatal cardiac interventions in humans: early definitive repairs of selected congenital heart disease may be more beneficial for the long-term results of surgical treatment.
Keywords: hypertrophy; phylogeny; cardiac development; adaptive growth response; hyperplasia; adaptation to overload; postnatal ontogeny